(untitled) (Conference Zone, 2022)
Using pneumatic transport, the raw material of cotton, which enters the working chamber of the baler in bulk, is crushed by mechanical processing with the help of a shaped cutter on the blade drum shaft mounted on the device in order to reduce seed damage.